Misremembering. (2nd April 2016) - Robins, Sarah K.
Abstract: The Archival and Constructive views of memory offer contrasting characterizations of remembering and its relation to memory errors. I evaluate the descriptive adequacy of each by offering a close analysis of one of the most prominent experimental techniques by which memory errors are elicited—the Deese-Roediger-McDermott (DRM) paradigm (Deese, 1959 ; Roediger & McDermott, 1995 ). Explaining the DRM effect requires appreciating it as a distinct form of memory error, which I refer to as misremembering. Misremembering is a memory error that relies on successful retention of the targeted event. It differs from both successful remembering and from confabulation errors, where the representation produced is wholly inaccurate. As I show, neither the Archival nor the Constructive View can account for the DRM effect because they are insensitive to misremembering's unique explanatory demands. Fortunately, the explanatory limitations of the Archival and Constructive Views are complementary. This suggests a way forward. Explaining misremembering—including how it differs from both successful remembering and confabulation—requires a hybrid theory of memory, combining the Archival commitment to discrete retention with the Constructive approach to retrieval. I conclude the paper with the beginning sketches of such an account.